2008
DOI: 10.1002/ijc.23804
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation of CDH13 is a common, early event in human esophageal adenocarcinogenesis and correlates with clinical risk factors

Abstract: Although the CDH13 gene has been shown to undergo epigenetic silencing by promoter methylation in many types of tumors, hypermethylation of this gene in Barrett's-associated esophageal adenocarcinogenesis has not been studied. Two hundred fifty-nine human esophageal tissues were therefore examined for CDH13 promoter hypermethylation by real-time methylation-specific PCR. CDH13 hypermethylation showed discriminative receiveroperator characteristic curve profiles, sharply demarcating esophageal adenocarcinoma (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 27 publications
6
34
0
1
Order By: Relevance
“…Highly invasive growth pattern (Berx et al 1998) Up-regulated expression Epithelial ovarian cancer (Sato et al 1998;Maruyama et al 2001;Toyooka et al 2001;Toyooka et al 2002;Roman-Gomez et al 2003;Hibi et al 2004;Sakai et al 2004;Kim et al 2005;Wang et al 2007;Brock et al 2008;Jin et al 2008;Yan et al 2008) LOH and promoter methylation Ovary Skin (BCC and SCC) Diffuse large B cell lymphoma HCC Tumor invasion; increased cell proliferation and resistance to apoptosis (Kawakami et al 1999;Takeuchi et al 2002a;Takeuchi et al 2002b;Ogama et al 2004;Chan et al 2008) Expression in intratumoral endothelium…”
Section: Somatic Mutations Breast (Ilc) Gastric (Dgc) Pancreasmentioning
confidence: 99%
“…Highly invasive growth pattern (Berx et al 1998) Up-regulated expression Epithelial ovarian cancer (Sato et al 1998;Maruyama et al 2001;Toyooka et al 2001;Toyooka et al 2002;Roman-Gomez et al 2003;Hibi et al 2004;Sakai et al 2004;Kim et al 2005;Wang et al 2007;Brock et al 2008;Jin et al 2008;Yan et al 2008) LOH and promoter methylation Ovary Skin (BCC and SCC) Diffuse large B cell lymphoma HCC Tumor invasion; increased cell proliferation and resistance to apoptosis (Kawakami et al 1999;Takeuchi et al 2002a;Takeuchi et al 2002b;Ogama et al 2004;Chan et al 2008) Expression in intratumoral endothelium…”
Section: Somatic Mutations Breast (Ilc) Gastric (Dgc) Pancreasmentioning
confidence: 99%
“…The PCR products were 82 bp long. To analyze the methylation status of the p16 gene [5], E-cadherin gene [6], RASSF1A gene [7], H-cadherin gene [22], DAPK gene [23], MGMT gene [23], and DCC gene [24], primers and conditions as described previously were used. The PCR products were separated by electrophoresis through a 9% polyacrylamide gel and stained with ethidium bromide.…”
Section: Bisulfite Modification and Msp Analysismentioning
confidence: 99%
“…Contrary to this, epigenetic effects, such as global hypomethylation and promoterspecific hypermethylation that are more dynamic in nature, or microRNA will likely be better markers to assess the efficacy of a chemopreventive agent. 58,[104][105][106][107][108][109] Recent studies have demonstrated progressive increase in the levels of GLI-1, vascular endothelial growth factor, transcription factor MCM2, COX-2 enzyme, PGE2, polyamine, 3,87 and upregulation of prosurvival NF-kB during oncogenesis in BE. 108 These biochemical and molecular markers of neoplastic progression also can assess if the molecular pathways intended to be targeted by chemopreventive agents are actually being downregulated.…”
Section: Surrogate Endpoint Biomarkersmentioning
confidence: 98%